2011
DOI: 10.4254/wjh.v3.i2.38
|View full text |Cite
|
Sign up to set email alerts
|

Liver cancer: Targeted future options

Abstract: Hepatocellular carcinoma (HCC) has a poor prognosis and systemic chemotherapies have disappointing resul ts. The increasing knowledge of the molecular biology of HCC has resulted in novel targets, with the vascular endothelial growth factor and epidermal growth fac tor receptor (EGFR)related pathways being of special interest. New blood vessel formation (angiogenesis) is essential for the growth of solid tumors. Antiangiogenic strategies have become an important therapeutic mo dality for solid tumors. Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Because many substrates for GALNT2 are present in HCC cells, it remains possible that GALNT2 mediates its effects through other receptors in addition to EGFR. EGFR inhibitors prevent the development of HCC in animal models (26) and erlotinib has shown some activity in the treatment of human HCC (16,27). Sorafenib, a multikinase inhibitor, has been shown to provide a significant survival benefit for patients with advanced HCC (28).…”
Section: Discussionmentioning
confidence: 99%
“…Because many substrates for GALNT2 are present in HCC cells, it remains possible that GALNT2 mediates its effects through other receptors in addition to EGFR. EGFR inhibitors prevent the development of HCC in animal models (26) and erlotinib has shown some activity in the treatment of human HCC (16,27). Sorafenib, a multikinase inhibitor, has been shown to provide a significant survival benefit for patients with advanced HCC (28).…”
Section: Discussionmentioning
confidence: 99%
“…The agent has been approved by the FDA for the treatment of renal cell carcinoma and refractory gastrointestinal stroma tumors [27]. Adverse effects were fatigue, hypertension, and skin toxicity, which are typical for VEGFR tyrosine kinase inhibitors.…”
Section: Antiangiogenic Agents and Therapymentioning
confidence: 99%
“…Besides antibody-based antiangiogenic agents, smallmolecule VEGF receptor tyrosine kinase inhibitors are another leading class of antiangiogenic drugs that have been investigated intensively in several preclinical and clinical studies in the last years: Sorafenib (Nexavar®) inhibits VEGF receptor 1-3, platelet-derived growth factor (PDGF) receptor β, Flt-3, and c-kit [26] and has verified activity in renal cell carcinoma (RCC) and hepatocellular carcinoma (HCC) [27]. Sorafenib was well tolerated with a maximal tolerated dose of 400 mg twice daily.…”
Section: Antiangiogenic Agents and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Vessels are markedly associated with the pathogenesis and development of tumors and it has been demonstrated that cells at the preneoplastic stage must acquire angiogenic capacity to become malignant cells. Without blood vessels, tumors cannot grow and form metastases (12)(13)(14). Vascular endothelial growth factor (VEGF) is the most important factor for the induction and regulation of proliferation of vascular endothelial cells as well as angiogenesis in physiological and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%